Positive smoker identity : a development and validation of smoking cessation instrument, and its associated factors - Ahmad, Mohd Hanief (2018)
Smoking cessation was important because smoking has been the single most essential preventable cause of premature death and morbidity. Positive Smoker Identity was a new construct representing positive smoker thoughts, images and feeling about smoking behaviour and culture. The objectives of this study were to evaluate the psychometric properties of a questionnaire developed to measure Positive Smoker Identity among smokers in government agencies in Kota Bharu, Kelantan, and to study its prevalence and associated factors. A cross-sectional study was carried out from March 2017 to March 2018 using data collected from smokers. The respondents answered a set of proforma and questionnaires including PSmoQi, which was initially developed and tested for content, face and construct validity in a pilot study. Data were analysed using R Software Version 3.3.1. Two-hundred and fifty-three smokers, who were all male and Malay, participated in the study. Majority of them had attained secondary school education or lower (52.2%), were of lower job level (70%), were married (88.9%), smoked cigarette daily (74.7%), used conventional cigarette (96.4%), smoked at home (68%), got their cigarettes from shop (90.9%), reported good health status (83.4%), occasionally saw smoking cessation campaign in the media (52.2%), and used mostly cheaper-than-market-price cigarette (55.3%). The best factor solution confirmed for the PSmoQi items was a 6-factor solution, with an overall Cronbach’s alpha of 0.77. PSmoQi was shown to have acceptable convergent validity, good divergent validity, and adequate concurrent validity with Smoker Self-Concept Scale (SSCS-M). The prevalence of respondents with Positive Smoker Identity was 72.3%. Factors associatedwith Positive Smoker Identity were age (AOR: 1.042; 95% CI: 1.004, 1.081); p = 0.028), SSCS-M score (AOR: 1.216; 95% CI: 1.112, 1.329; p < 0.001), heaviness index (AOR: 1.002; 95% CI: 1.001, 1.004; p = 0.011), and educational attainment. (AOR: 0.458; 95% CI: 0.233, 0.900; p = 0.024). In summary, PSmoQi was a valid and reliable instrument to measure a comprehensively rich and deep Positive Smoker Identity construct, and would facilitate parametric statistical analyses in future studies on smoking cessation.